Soviet Repatriation Efforts among "Displaced Persons" Resettled in Australia, 1950–53. (March 2017) - Fitzpatrick, Sheila
Abstract : In the early 1950s, the Soviet Union made great efforts to persuade its former citizens among the "displaced persons" (DPs) resettled in Australia after the war to repatriate. They sent two undercover military intelligence men to Canberra to identify DPs who might be interested in returning, offer them free passages, and organize the repatriation. The result was a paltry dozen repatriations, out of the estimated 50, 000 eligible DPs resettled in Australia. This strange story — hitherto completely unknown and reconstructed on the basis of recently opened Soviet classified material in the State Archive of the Russian Federation and ASIO files in the National Archives of Australia — adds a new angle to our understanding of Soviet‐Australian (and, in general, Soviet‐Western) relations at the height of the Cold War.